Superoxide producing associate between NADPH oxidase and NADPH containing lipoprotein (NCL) from human blood erythrocytes and leukocytes membranes: activation of immune cells by NCL - Simonyan, R. M.; Chailyan, S. G.; Chavushyan, V. A.; Simonyan, K. V.; Isoyan, A. S.; Babayan, M. A.; Simonyan, G. M.; Simonyan, M. A. (Հայաստանի ԳԱԱ «Գիտություն» հրատ.)
From erythrocyte membranes (EM) and leukocyte membranes (LM) of human donor blood of group II the superoxide (О2 -)- producing associate of NADPH oxidase (Nox) with NADPHcontaining lipoprotein – NCL (Nox-NCL) was isolated and purified for the first time. Water solutions of the Nox-NCL have weak opalescence at pH 9.5. The specific content of the Nox-NCL from EM and LM is 3.6±0.04 mg/ml of erythrocytes, and from LM – 21.5±2.9 mg / ml of leucocytes (p<0.05, n=6). The specific O2 - -producing activity of the Nox-NCL EM is 30.2± 1,6 units/mg and 40,4±5,0 units/mg of these membranes, correspondingly (p<0.05, n=6). The mechanism of the production of O2 - by these Nox-NCL associates contidioned by transfer of an electron from NADPH of this NCL to Fe(+3) of heme group of the Nox, then to molecular oxygen, reducing it to O2 -. Առաջին անգամ մարդկային դոնորական արյան II խմբի էրիթրոցիտների թաղանթներից (ԷԹ) ու լեյկոցիտների թաղանթներից (ԼԹ) անջատվել և մաքրվել է սուպերօքսիդ (2-)-գոյացնող ասոցիատ՝ կազմված ՆԱԴPH օքսիդազից (Nox) և ՆԱԴPH-պարունակող լիպոպրոտեինից-ՆՊԼ (NoxՆՊԼ): Nox-ՆՊԼ ասոցիատի ջրային լուծույթները pH 9,5-ում ունեն թույլ օպալէսցենցիա: Nox-ՆՊԼ-ի տեսակարար քանակը ԷԹ-երում և ԼԹ-երում համապատասխանաբար կազմում է 30.2±1,6 մգ/մլ և 21.5±2.9 մգ/1մլ, (p<0.05, n=6). ԷԹ-երից և ԼԹ-երից անջատած Nox-ՆՊԼ-ի տեսակարար O2-.-գոյացման ակտիվությունը համապատասխանաբար կազմում է 30.2±1,6 մ/մգ և 40,4±5,0 մ/մգ (p<0.05, n=6). Այդ ասոցիատներով O2-. -գոյացման մեխանիզմը պայմանավորված է ՆՊԼ-ի ՆԱԴPHից էլեկտրոնի փոխանցմամբ դեպի թաղանթային Nox-ի հեմային խմբի Fe(+3), որից էլ դեպի մոլեկուլային թթվածին՝ վերականգնելով այն մինչև O2- : Впервые из эритроцитарных мембран (ЭМ) и лейкоцитарных мембран (ЛМ)донорской крови человека II группы выделен и очищен супероксид (О2-)-продуцирующий ассоциат NADPH оксидазы (Nox) с NADPH-содержащим липопротеином – НСЛ (NoxНСЛ). Водные растворы ассоциата Nox-НСЛ имеют слабую опалесценцию при pH 9,5. Удельное содержание Nox-НСЛ из ЭМ и ЛМ составляют 3,6±0,04 мг/мл и 21.5±2.9мг/мл (p<0.05, n=6) соответственно. Удельная O2 --продуцирующая активность Nox-НСЛ из ЭМ и ЛМ составляет 30.2±1,6 ед/мг и 40,4±5,0 ед/мг (p<0.05, n=6) соответственно. Механизм продуцирования O2 -этими ассоциатами Nox-НСЛ обусловлен передачей электрона от NADPH из НСЛ к Fe(+3) гемовой группы Nox, далее к молекулярному кислороду, восстанавливая его до O2-.
Keywords: Biochemistry